Effects of biological treatments on water quality in neotropical fishponds - Sipaúba-Tavares, Lúcia Helena [UNESP]; Millan, Rodrigo Ney [UNESP]; Penariol, Iara Carolina [UNESP] (My University, 2015)
The aim of this study was to investigate the effects of the aquatic macrophyte (Eichhornia crassipes) and periphyton communities on the neotropical fishponds water quality, and to determine the ability of such communities to remove potential pollutants from the fishponds, making them interesting tools for the maintenance of desirable water quality in aquaculture under continuous water flow. In general, the biological treatments used in this study showed a positive effect in reducing BOD5, orthophosphates, total phosphorus, conductivity and thermotolerant coliforms from the water column and also decreasing organic matter, Cu, Fe, Mn and Zn, from the sediment. The differences in physical and chemical properties of the water column and sediment between the treatments showed an improvement in the overall water quality when the treated fishponds are compared with the control fishpond. The best growth rate performance of Nile tilapia (Oreochromis niloticus) occurred in the fishpond with periphyton treatment.
Keywords: Aquaculture; Macrophytes; Nile tilapia; Periphyton